Lethal chondrodysplasia punctata in two siblings - Tekinalp, Gülsevin; Erdem, Gülşen; Balcı, Sevim; Çağlar, Melda; Diren, Barış; Dizdarer, Ceyhun; Toppare, Mete (The Turkish Journal of Pediatrics, 1987)
This report describes two siblings affected by the rhizomelic type of chondrodysplasia punctata who were born of healthy parents. To our knowledge these are the first cases in two siblings presenting with this rare syndrome reported in our country.